Effectiveness of a Hydrophilic Curcumin-Based Formulation in Coadjuvating the Therapeutic Effect of Intravitreal Dexamethasone in Subjects With Diabetic Macular Edema - Parravano, Mariacristina; Allegrini, Davide; Carnevali, Adriano; Costanzo, Eliana; Giannaccare, Giuseppe; Giorno, Paola; Scorcia, Vincenzo; Spedicato, Giorgio Alfredo; Varano, Monica; Romano, Mario R (Frontiers in Pharmacology, 2022)
Purpose: This study evaluates if the addition of a curcumin formulation with a polyvinylpyrrolidone-hydrophilic carrier (CHC; Diabec®, Alfa Intes, Italy) to intravitreal injections of dexamethasone (DEX-IVT) can affect the morphological retinal characteristics, extending the steroid re-treatment period in patients with diabetic macular oedema (DME). Methods: A randomized controlled clinical trial was carried out in DME patients, randomly assigned to receive DEX-IVT or DEX-IVT and CHC. The evaluation of the mean difference of central retinal thickness (CRT) was the primary aim. Secondary aims were the evaluations of best-corrected visual acuity, differences in the predetermined retinal layers thickness, the number/time of retreatment and the assessment of safety. Results: 73 DME patients were included (35 in the control group and 38 in the combined therapy group). In both groups, the mean CRT change from T0 to the 6-month evaluation was significant (p=0.00). The mean CRT resulted significantly different at month 4 (p=0.01) between groups, with a greater reduction in the combined therapy group, in particular, in patients with ≤10 years diabetes. A trend of CRT reduction in the combined therapy group has been observed also considering patients with subfoveal neuroretinal detachment. In addition, we observed that the reduction of inner retinal layer thickness was greater in the combination group, in comparison with controls. Conclusion: The combination of a CHC to DEX-IVT is a promising therapeutic option in case of DME, in particular, for patients with early-stage diabetes and with an inflammatory phenotype. Further studies will be necessary to confirm these findings.